Sistemas agrícolas y alimentarios sostenibles del páramo cochapungo de la comunidad atocha, año 2021 - Herrera Amores, Diego Andrés (2021)
The páramo is a substantial ecosystem because of the diverse environmental services it offers us, where agricultural and livestock activities are of important necessity for the food satisfaction of the population. This research was developed with the objective of evaluating the sustainable agricultural and food systems of the Cochapungo páramo of the Atocha community, year 2021. The Delphi methodology allowed to gather a group of five people to use their experience and knowledge to select the indicators that cover the four sustainability domains (governance, environmental, economic and social). The SAFA methodology allowed the application of the previously selected indicators to generate the sustainability polygon. The results were very satisfactory since the qualification of each indicator was carried out with the support of a survey, which was used to argue and collect the criteria of the people living in the community of Atocha who carry out their agricultural activities in the Cochapungo moor. Based on the above, it could be concluded that the reality of the place where the research was carried out has a good level of sustainability, it is recommended to improve certain issues such as good governance. Key words: domains, methodology, indicators, Delphi, SAFA.